2018
DOI: 10.30657/pea.2018.18.08
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hardness of magnesium alloys due to precipitation hardening

Abstract: This paper deals with the evaluation of changes in hardness of magnesium alloys during precipitation hardening that are nowadays widely used in different fields of industry. It focuses exactly on AZ31, AZ61 and AZ91 alloys. Observing material hardness changes serves as an effective tool for determining precipitation hardening parameters, such as temperature and time. Brinell hardness measurement was chosen based on experimental needs. There was also necessary to make chemical composition analysis and to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The curve also lacks the necessary underaged and overaged sections required for ageing response, as such showing that these alloys were not age hardenable. This was as expected due to the compositional similarity to the AZ31 range of alloys, which are typically used in wrought applications and are known for a lack ageing response[37].…”
supporting
confidence: 75%
See 4 more Smart Citations
“…The curve also lacks the necessary underaged and overaged sections required for ageing response, as such showing that these alloys were not age hardenable. This was as expected due to the compositional similarity to the AZ31 range of alloys, which are typically used in wrought applications and are known for a lack ageing response[37].…”
supporting
confidence: 75%
“…This is observed in Figure 9 through a typical age hardening curve featuring underaged, peak and overaged sections. [37] Studies show that with Mg-Al alloys it is expected that Mg17Al12 precipitates must be reduced, since these are responsible for poor creep resistance properties. Other studies have shown that small amounts of cold working prior to ageing can sharply increase the rate of hardening, however this is beyond the scope of this project and any striking resulting in permanent tensile strain has been actively avoided [38].…”
Section: Age Hardeningmentioning
confidence: 99%
See 3 more Smart Citations